Financing Aspects of an Effective Strategy for Innovative Enterprise Development - TURGINBAYEVA, Ardak; USTEMOROV, Asset; AKHMETOVA, Gulmira; KOSE, Zhanna; IMASHEV, Aibek; GIMRANOVA, Galiya (Journal of Advanced Research in Law and Economics, 2018)
The current stage in the formation of Kazakhstan's market economy requires the creation of an innovation policy system. State innovation policy is understood as a set of goals, as well as methods of influence of state structures on the economy and society as a whole related to initiating and increasing the economic and social effectiveness of innovation processes. Innovative policy becomes important in conditions of increasing innovation activity of commercial and state enterprises and structural restructuring of the country as a whole. Earlier, in the conditions of non-market relations in the economy of the Republic of Kazakhstan, innovative processes were centrally managed by state administrative bodies (ministries, state committees, main administrations, administrations of all levels), as well as their representatives at state enterprises represented by directors. The transition to the market strengthens technological competition, leads to the bankruptcy of those who use and produces obsolete products, and provides super profit (based on differential scientific and technical income) to pioneers of scientific and technological progress, active innovators. The author investigates the question of increasing the innovation potential of public policy in terms of enterprises development. Special attention is paid to financial aspects of this innovation strategy.